The Effect of Google Earth Utilization on Students' Spatial Thinking Ability - Sri Rahayu; M Murjainah; M Idris (Geosfera Indonesia, 2019)
The ability to think spatially in geography learning is essential, so it requires technology-based learning resources in the form of google earth, which can facilitate students in imagining or visualizing images in mind. In this regard, this study aims to determine the effect of the use of google earth on the spatial thinking abilities of students in the class X Geography of SMA PGRI 2 Palembang. This study used an experimental research method (Posttest-Only Control Design), because this design is suitable to use if the pre-test is not possible or pre-test can influence the experimental. The sample data collection technique uses Purposive Sampling, which is based on considerations or criteria that must be met by the sample used in the study. The sample in this study is class X IPS 1 as the experimental class and X IPS 2 as the control class. Data collection techniques use documentation and tests. For data analysis techniques, normality test, homogeneity test, and hypothesis testing using the IBM SPSS Statistics 20 formula for Windows. Based on the results of the study, the average value of the experimental class's superior post-test was 82.92, and the results of the posttest control class were 66.39. It shows that there are differences in the spatial thinking ability of the experimental group students who were treated using Google Earth during the learning process. The significance of the results of the posttest t-test from the two experimental and control groups was 0.000, and then the null hypothesis Ho was declared rejected because based on the t-test criteria, the significance value was <0.05 or the Sig (2-tailed) value of 0,000 was obtained <0.05. So it can be concluded that there is a significant influence between the use of google earth on the spatial thinking ability of students in the class X Geography subject of SMA PGRI 2 Palembang. Keywords: Google Earth, Spatial Thinking Ability, Geography. References Aliman, Mutia, & Yustesia. (2018). Integrasi Kebangsaan Dalam Tes Berpikir Spasial. Jurnal Geografi FKIP UMP , 82-89. Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta. Ardyodyantoro, Gatty. (2014). Pemanfaatan Google Earth Dalam Pembelajaran Geografi Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Widya Kutoarjo. Skripsi. Program Studi Pendidikan Geografi Fakultas Ilmu Sosial Universitas Negeri Yogyakarta. Cuviello, Matthew P. (2010). Evaluating Google Earth in the Classroom. New York : Center for Teaching Excellence Ervina, E., Asyik, B., & Miswar, D. (2012). Pengaruh Penggunaan Media Google Earth Dan Peta Terhadap Peningkatan Hasil Belajar Geografi. JPG (Jurnal Penelitian Geografi), 1(1). Hidayat, K. N., & Fiantika, F. R. (2017). Analisis Proses Berfikir Spasial Siswa Pada Materi Geometri. Prosiding Si Manis (Seminar Nasional Integrasi Matematika dan Nilai Islami) , 385-394. Isnaini, N. (2018). Komparasi Penggunaan Media Google Earth Dengan Peta Digital Pada Materi Persebaran Fauna Kelas XI IPS di SMA Negeri 1 Semarang. Jurnal Geografi: Media Informasi Pengembangan Dan Profesi Kegeografian, 12(1), 52-61. Jo, I., & Hong, J. E. (2018). Geography Education, Spatial Thinking, and Geospatial Technologies: Introduction to the Special Issue. International Journal of Geospatial and Environmental Research, 5(3), 1. Liu, R., Greene, R., Li, X., Wang, T., Lu, M., & Xu, Y. (2019). Comparing Geoinformation and Geography Students’ Spatial Thinking Skills with a Human-Geography Pedagogical Approach in a Chinese Context. Sustainability, 11(20), 5573. doi:10.3390/su11205573 Nofirman, N. (2019). Studi Kemampuan Spasial Geografi Siswa Kelas XII SMA Negeri 6 Kota Bengkulu. Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 3(2), 11-24. Oktavianto, D. A. (2017). Pengaruh Pembelajaran Berbasis Proyek Berbantuan Google Earth Terhadap Keterampilan Berpikir Spasial. Jurnal Teknodik, 21(1), 059. Patterson, T. C. (2007). Google Earth as a (Not Just) Geography Education Tool. Journal of Geography, 106(4), 145–152. doi:10.1080/00221340701678032 Setiawan, I. (2016). Peran Sistem Informasi Geografis (Sig) Dalam Meningkatkan Kemampuan Berpikir Spasial (Spatial Thinking). Jurnal Geografi Gea, 15(1). doi:10.17509/gea.v15i1.4187 Sugiyono. (2010). Metode Penelitian Pendidikan Pendekatan Kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta. Sudjana. (2005). Metode Statistika. Bandung: Tarsito. Yousman, Y. (2008). Google Earth. Yogyakarta: C.V Andi. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License